Imagery in Uhibbuki wa Kafā: A Stylistic Study of Muhammad Al-Salem’s Poetry - Fitri, Aulia Anggina; ., Zubair (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
This study aims to describe imagery in the poems of Muhammad Al-Salem contained in the poetry anthology Uhibbuki wa Kafā. Imagery in literature may take the form of sensory imagery as well as mental imagery, each with diverse types and meanings. This research is limited to four selected poems from the anthology Uhibbuki wa Kafā because they contain abundant and compelling imagery. The method employed in this study is a qualitative descriptive approach, and stylistic analysis is used as the analytical framework. Based on the data and analysis, it can be concluded that there are 71 instances of imagery identified in the four poems examined. All types of sensory imagery are present, namely: 27 visual images, 16 auditory images, 6 kinesthetic images, 4 olfactory images, 3 tactile images, and 1 gustatory image. In addition, 14 instances of mental imagery in the form of intellectual imagery are also found. Each type of imagery identified possesses its own distinctive characteristics that contribute to the richness and beauty of the poems, significantly enhancing their aesthetic value.